Implementation Of Arabic And English Learning To Improve The Speaking Skills Of Female Students At Nurus Salafiyah Islamic Boarding School Probolinggo City - Zainuddin, Zainuddin; Wafi, Abdul (Insya : Journal of Arabic Studies, 2024)
Implementation of Arabic and English learning as a solution to improve female students' speaking skills has the aim of developing female students' skills in Arabic and English. So that female students can have knowledge of language that can be used according to Arabic and English rules. Nurus Salafiyah Islamic Boarding School has provided various kinds of knowledge about learning Arabic and English so that its female students become language role models and have improved language skills. This research was written using a qualitative research method with a descriptive approach that explains learning Arabic and English to enhance the skills of female students at the Female Nurus Salafiyah Islamic boarding school, in Probolinggo city. Based on the results of an analysis of this research, the Implementation of learning Arabic and English is an essential foundation for improving language skills and providing knowledge about language through the correct learning of Arabic and English rules. Arabic and English education, which is the process of female students receiving knowledge, comes from implementing their learning and facilitators who always provide motivation and learning to the female students at the Female Nurus Salafiyah Islamic boarding school, Probolinggo City. This shapes the students' personalities to continue to develop in improving their language skills in various aspects of science which are all related to Arabic and English.